Eksplorasi Penggunaan Aplikasi Canva dalam Meningkatkan Desain Pesan Pembelajaran - Yuzi Hana Christiani; Ajerin Karim; R.R Eka Ratnawati; Warneri Warneri; Eny Enawaty (Journal on Education, 2024)
One of the increasingly popular applications used for learning is Canva, this application is an online design application that is easy to use, and can help teachers create learning materials that are visually attractive and interactive, thereby increasing student motivation and learning outcomes. The aim of this research is to find out whether there is a relationship between the level of teacher familiarity with the Canva application and the teacher's skills in designing interesting learning messages; and identifying teachers' perceptions of the effectiveness of using the Canva application in improving the quality of learning message design. This research uses a quantitative descriptive method with a survey research type. The research sample was 30 teachers at SMP Negeri 1 Mempawah Hilir. The data that has been collected is processed and analyzed using IBM SPSS. The research results showed that the average value for the familiarity aspect with the Canva application was 91.3% in the high category. The average value of usage level and frequency is 95.2% in the high category. The average score for the creativity aspect and impact of the Canva application in classical learning is 99.5% in the high category. The average value of the challenge and support aspect is 81.8% in the high category. The conclusion obtained is that there is a relationship between the teacher's level of familiarity with the Canva application and the teacher's response to the Canva application is very good.